2015
DOI: 10.1007/s11626-015-9925-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of astrocyte activity via control over stiffness of cellulose acetate electrospun nanofiber

Abstract: Astrocytes are involved in neuron protection following central nervous system (CNS) injury; accordingly, engineered astrocytes have been investigated for their usefulness in cell therapy for CNS injury. Nanofibers have attracted a great deal of attention in neural tissue engineering, but their mechanical properties greatly influence physiology. Cellulose acetate (CA) has been studied for use in scaffolds owing to its biocompatibility, biodegradability, and good thermal stability. In this study, stiffness of CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…5c–g ). These findings are intriguing given the clinical observation that several Alexander disease patients have begun to exhibit disease signs and symptoms following brain trauma 41 , and are consistent with astrocyte sensitivity to substrate stiffness 42 , 43 .…”
Section: Discussionmentioning
confidence: 74%
“…5c–g ). These findings are intriguing given the clinical observation that several Alexander disease patients have begun to exhibit disease signs and symptoms following brain trauma 41 , and are consistent with astrocyte sensitivity to substrate stiffness 42 , 43 .…”
Section: Discussionmentioning
confidence: 74%
“…Liu et al showed that astrocytes decrease GFAP expression when cultured on aligned and randomly oriented electrospun collagen fibers, compared to flat collagen-coated glass coverslips [187]. Similar results were also observed when astrocytes were plated on randomly oriented cellulose acetate electrospun fibers [188] and PCL electrospun fibers [189] compared to flat surface controls. Conversely, a recent study by Gottipati et al further characterized astrocytic response to electrospun fibers by studying the expression of various reactive astrocyte phenotypic markers; they showed that the astrocytes cultured on aligned PLLA fibers display a more neurotoxic reactive phenotype compared to PLLA films [190].…”
Section: Astrocyte Response To Electrospun Fibers In Vitromentioning
confidence: 72%
“…Loading cellulose-based biomaterials with drugs is a promising avenue for drug delivery (Naseri-Nosar et al, 2017). The tunable mechanical properties, highly porous structure, adjustable stability, and excellent biocompatibility make cellulose an ideal candidate for nerve tissue repair and drug delivery systems (Wang et al, 2013; Du et al, 2014; Min et al, 2015; Kuzmenko et al, 2016; Naseri-Nosar et al, 2017). Significantly, it has been shown that cellulose constructs can be used as nerve guidance conduits for sciatic nerve defects in rats (Naseri-Nosar et al, 2017).…”
Section: Applicationsmentioning
confidence: 99%